(untitled) (Research, Society and Development, 2022)
Dengue is an infectious disease caused by a virus transmitted by the Aedes aegypti mosquito and has great geographic potential, especially in tropical and subtropical regions. The present study consists of a scope review protocol and aims to identify and characterize the phytochemical substances with the greatest larvicidal potential against Aedes aegypti. This scoping review will build on proposals from The Joanna Briggs Institute (JBI) and will follow the recommendations of the PRISMA Extension for Scoping Reviews (PRISMA-ScR) checklist items. Articles in English, Portuguese and Spanish used to support this research will be selected from the following databases: Web of Science, PubMed and Lilacs. This scope review will provide a mapping of the scientific production on dengue in the world, during the period from 2012 to 2022. This study will address the classes of phytochemical compounds effective in controlling of Aedes aegypti and the presentation of the mechanism of action of these larvicides. This protocol is registered in the Open Science Framework (OSF), with doi: https://10.17605/OSF.IO/Y9PUW.It is hoped with this article to provide subsidies for choosing the best substance of natural origin for effective control of this mosquito that causes diseases of extreme concern to public health.